Sex differences in performance and pacing strategies during a sprint time-trial in cross-country skiing - Andersson, E. P.; Govus, A.; Shannon, O. M.; McGawley, K. (23rd annual Congress of the European College of Sport Science ECSS, Dublin, 4-7th July, 2018, 2018)
INTRODUCTION: The aim of this study was to compare the pacing strategies, choice of sub-technique (i.e., gear) and overall performance between elite male and female cross-country (XC) skiers during a ski-skating sprint time-trial (TT) on snow.